THE RELATIONSHIP BETWEEN THE CATEGORIES “EDUCATIONAL ENVIRONMENT” AND “EDUCATIONAL SPACE” IN RUSSIAN PSYCHOLOGICAL AND PEDAGOGICAL SCIENCE - Valentinovna Ivanova, Natalia; Mikhailovna Sorokina, Tatiana (Revista Inclusiones, 2020)
The article presents the results of theoretical research aimed at studying the correlation between the semantics of the terms “educational space” and “educational environment” in Russian scientific publications. The relevance of the differentiation of these terms is determined by their introduction into the regulatory documents governing Russian education, the variability of their interpretations in the scientific literature, and their insufficient understanding by practicing teachers. Theoretical analysis is used as the primary research method. It is determined that a number of scholars define the concept “educational space” through the concept “educational environment” and some Russian researchers use these concepts as synonymous. The conducted analysis allows identifying a number of significant similarities in said categories: focus on the educational objectives, translation of social experience, systemic structure, irreducibility to the social aspect alone, dynamism and variability, ability to act as an object of modeling, presence of various levels of functioning, ability to serve a developmental function under certain conditions.